(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
People’s Republic of China has a great role in the modem world. Its history in XX century was full of bloody events in the struggle for elimination of foreign influence. As weil as, in China were fighting long wars which claimed a lot of death-toll. In this period many persons were distinguished themselves and leaved their mark on the contemporary history of the PR China. PR China during this period had performed many reforms which were reflected on economic situation in the country especially this was typically in the period after the Second World War. At the same teme, China was in active foreign politics for breakout in the external world.